Menggali Model Ritual Usahatani Jagung Sebagai Simbol Identitas Petani di Kabupaten Timor Tengah Utara - Falo, Marsianus; Kolne, Salesius Vitalis (Fakultas Pertanian, Universitas Timor, 2024)
This research begins with the phenomenon of farmers in North Central Timor Regency who apply local wisdom in corn farming ritual activities as a belief inherited from their ancestors who believe they have the power to rely on natural spirits as guardians of the nature where they live, including in guarding the corn farming that is being carried out. This research aims to determine the description of the local wisdom model of rituals held by farmers in corn farming. Sampling was carried out among corn farmers using the technique: first, determining key informants using Snowball Sampling as many as 7 people. Second, the determination of informants was carried out purposively, aimed at 10 figures related to corn farming, so the total number of respondents was 17 people. Primary data was collected using a questionnaire guide, in-depth interviews (FGD) and secondary data was obtained from the Agriculture Service, BPS and related agencies. The results of the analysis show that the local wisdom model for changing farmer behavior has not worked optimally. And farmers in general are aware that the rituals of corn farming activities are carried out in accordance with their beliefs and beliefs and have been carried out for generations taking into account the farming cycle they have and greatly influence changes in farmers' behavior in corn farming. Harmonious farmer relations in carrying out corn farming rituals are currently being carried out but in certain parts it has not yet gone as expected, namely the Tapoen Fini ritual (Removing Seeds), Pen Sufa' (Time for Corn to Flower), Tah Fe'u (new food), T 'sek Pena (Breaking Corn), Takbu' Pena (harvesting corn), Tsef Pena smanaf (Opening the Spirit of Corn), T'hab nin (preparation for storage), Ta sae be noe Lopo (putting into Lopo).